Entrelaçamentos de vidas : a constituição da docência na educação profissional e tecnológica - Fortes, Maria Carolina (2012)
The research intends to announce the formation processes of teaching in Professional and Technological Education, having IFSUL Campus Passo Fundo, as the focus of study. It aims to understand how teaching constitutes the life trajectories of six teachers engaged in this type of education, the connections between schooling in childhood and adolescence in entanglements with the process of choosing a career in teaching and later reconfiguration as this choice in perspective to view the experiences of life, expressed in individual careers, as producers of constitutive meanings of teaching. This is a qualitative research and draws on the principles of ethnography, and search visibility to "Meanings Network" and (auto)biographical studies and theoretical-methodological perspective; develops through the life narratives of teachers and used as main strategies document analysis, observations and narrative interviews, which constituted the mode of apprehension and analysis. The data analysis is in the dialogue with the life stories and theoretical research in particular: Rossetti-Ferreira, Melucci, Elias, Freire, Abraham, Bosi, Ricoeur, Bolivar, Delory-Momberger, Dominecê, Huberman, Josso , Nóvoa, Tardif, Lessard, Guauthier, Bruner, Giddens, Mires, Sarti, Charlot and Santos. Thus was made possible knowledge about the concreteness, similar and unique teaching process in the constitution intertwining meanings and knowledge constituted a processuality interactive configured in relation to their own teacher's knowledge accompanied by a social relationship that are articulated and reflective in making everyday experiences in teaching, because they are closely linked to knowledge about the work and functions of teachers as research demonstrates through narratives about the pedagogical actions - meetings, teacher training, class council and the classroom activities - in particularly highlighting the importance that teachers give to the experience. These senses are twists in establishing relationships in the school environment, making it remains: overcoming insecurity, the bonds of friendship, the listening and visibility space, the appreciation of singular/plural knowledge of teaching constructed along the paths of life, the participation in interactive spaces of Campus, the knowledge of teaching as articulator of other processes such as group life and instituting space of belonging. Thus the senses exceeded the constitution of a universe of knowledge-objects, approaching two other cases of epistemic relation to knowledge: the action in the World and the regulation of the relationship with others and with themselves. The research draws attention to the processes of teacher training in Professional and Technical Education is looked at from other perspectives - teachers as social and as such, subject to their formative processes, considering the relationships they establish with themselves and the world.